Establishing Simultaneous T Cell Receptor Excision Circles (TREC) and K-Deleting Recombination Excision Circles (KREC) Quantification Assays and Laboratory Reference Intervals in Healthy Individuals of Different Age Groups in Hong Kong - Kwok, Janette S. Y.; Cheung, Stephen K. F.; Ho, Jenny C. Y.; Tang, Ivan W. H.; Chu, Patrick W. K.; Leung, Eric Y. S.; Lee, Pamela P. W.; Cheuk, Daniel K. L.; Lee, Vincent; Ip, Patrick; Lau, Y. L. (Frontiers in Immunology, 2020)
The clinical experience gathered throughout the years has raised awareness of primary immunodeficiency diseases (PIDD). T cell receptor excision circles (TREC) and kappa-deleting recombination excision circles (KREC) assays for thymic and bone marrow outputs measurement have been widely implemented in newborn screening (NBS) programs for Severe Combined Immunodeficiency. The potential applications of combined TREC and KREC assay in PIDD diagnosis and immune reconstitution monitoring in non-neonatal patients have been suggested. Given that ethnicity, gender, and age can contribute to variations in immunity, defining the reference intervals of TREC and KREC levels in the local population is crucial for setting up cut-offs for PIDD diagnosis. In this retrospective study, four hundred and seventy-nine healthy Chinese sibling donors (240 males and 239 females; age range: 1 month to 74 years) from Hong Kong were tested for TREC and KREC levels using a simultaneous quantitative real-time PCR assay. Age-specific 5th - 95th percentile reference intervals of TREC and KREC levels (expressed in copies per µL blood and copies per 106 cells) were established in both paediatric and adult age groups. Significant inverse correlations between age and both TREC and KREC levels were observed in the paediatric age group. A significant higher KREC level was observed in females than males after 9-12 years of age but not for TREC. Low TREC or KREC levels were detected in patients diagnosed with mild or severe PIDD. This assay with the established local reference intervals would allow accurate diagnosis of PIDD, and potentially monitoring immune reconstitution following haematopoietic stem cell transplantation or highly active anti-retroviral therapy in the future.